INVENTARISASI MAKROFAUNA TANAH DI BAWAH TEGAKAN KARET (Hevea brasiliensis) PADA LAHAN GAMBUT - Saputra, Irawan Dede; Amri, Al Ikhsan; ', Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aimed to determine species of macrofauna and calculate population density of soil macrofauna understands of rubber plant in pet land in different ages. The research was conducted on 1 hectare area of peat land. It is divided in to two parts with ½ hectare 4 years rubber plant and ½ hectare 6 years rubber plant. The method that used is a survey method. Data was collected by purposive sampling. 9 plants samples were taken to each ages, and it get 18 plant samples. Soil sampling and soil macrofauna carried out in area 50 x 50 cm with depth 15 cm. The samples were taken around the plant samples (1 meter from the base of plant) and between plants (at rows). The method to collect of soil macrofauna by hand sortir method. Rubber plantations aged 6 years and 4 years have the same kind that are braid (Geophilomorpha), ants (Hymenoptera) and ground beetles (Coleoptera). Rubber plantations aged 6 years found 381 soil macrofauna more than rubber plantations aged 4 years found 289 soil macrofauna. Keywords: macrofauna, peat, rubber.